Cinnamaldehyde and α-terpineol inhibit the growth of planktonic cultures of Candida albicans and non albicans (Research, Society and Development, 2021)
Agents based in natural products have been investigated for the treatment of oral candidiasis. This study aims to evaluate the antifungal effect of phytoconstituent cinnamaldehyde and α-terpineol in planktonic cultures of Candida albicans, Candida glabrata, Candida krusei and clinical isolates of C. albicans. Reference strains of C. albicans (ATCC 90028 and ATCC 60193), C. glabrata (ATCC 2001), C. krusei (ATCC 34135) and four clinical isolates were used. Nistatin 100,000UI was used as a positive control.  After preparation of the inoculum (1 × 103 CFU / mL), serial microdilution technique was performed using RPMI 1640 medium. Results: in reference strains, the MIC for α-terpineol ranged from 312,5 μg / mL (C. albicans 90028) to 40 μg / mL (C. krusei); and the cinnamaldehyde ranged from 40 μg / mL (C. albicans 90028, C. albicans 60193 and C. glabrata) to 20 μg / mL (C. krusei). Whereas for clinical strains, the MIC for α-terpineol ranged from 156 μg / mL to 78 μg / mL and cinnamaldehyde ranged from 78 μg / mL to 40 μg / mL. Therefore, the cinnamaldehyde and α-terpineol present an inhibitory effect against planktonic cultures of Candida albicans and not albicans.